DISMISSAL FOR GROSS MISCONDUCT IN EMPLOYMENT UNDER THE 1992 LABOUR CODE OF CAMEROON: ANY NEED FOR REFORM? (IUS LAW Journal, 2025)
Section 36(2) of Cameroon’s Labour Code 1992 explicitly recognises that a contract of employment may be terminated in cases of gross misconduct subject to the findings of the competent court as regards the gravity of the misconduct. However, this section is ambiguous, and renders effective implementation in the context of Cameroon difficult, because it does not unambiguously encapsulate the grounds of a worker’s gross misconduct that may necessitate summary dismissal. Through the doctrinal research method, the paper critically examines the gravity of a worker’s misconduct that may necessitate dismissal as envisioned under section 36(2) of the Code. It reveals that the ambiguous nature of section 36(2) renders effective implementation in Cameroon difficult with grave consequences on workers’ rights. The paper recommends a revision of section 36(2) in order to clearly encapsulate the nature of a worker’s gross misconduct that may justify summary dismissal.
Keywords: Dismissal; Gross misconduct; Worker; Employment; 1992 Labour Code of Cameroon